Unraveling the genetic basis of heat tolerance and yield in bread wheat: QTN discovery and Its KASP-assisted validation - Bashir, Latief; Budhlakoti, Neeraj; Pradhan, Anjan Kumar; Mehmood, Azhar; Haque, Mahin; Jacob, Sherry R.; Bhardwaj, Rakesh; Gaikwad, Kiran; Dwijesh Chandra Mishra; Kaur, Satinder; Bhati, Pradeep Kumar; Singh, Gyanendra Pratap; et al. (BioMed Central Ltd., 2025)
Background: Wheat (Triticum aestivum L.), a globally significant cereal crop and staple food, faces major production challenges due to abiotic stresses such as heat stress (HS), which pose a threat to global food security. To address this, a diverse panel of 126 wheat genotypes, primarily landraces, was evaluated across twelve environments in India, comprising of three locations, two years and two growing conditions. The study aimed to identify genetic markers associated with key agronomic traits in bread wheat, including germination percentage (GERM_PCT), ground cover (GC), days to booting (DTB), days to heading (DTHD), days to flowering (DTFL), days to maturity (DTMT), plant height (PH), grain yield (GYLD), thousand grain weight (TGW), and the normalized difference vegetation index (NDVI) under both timely and late-sown conditions using 35 K SNP genotyping assays. Multi-locus GWAS (ML-GWAS) was employed to detect significant marker-trait associations, and the identified markers were further validated using Kompetitive Allele Specific PCR (KASP). Results: Six ML-GWAS models were employed for this purpose, leading to the identification of 42 highly significant and consistent quantitative trait nucleotides (QTNs) under both timely and late sown conditions, controlled by 20 SNPs, explaining 3-58% of the total phenotypic variation. Among these, noteworthy QTNs were a major grain yield QTN (qtn_nbpgr_GYLD_3B) on chromosome 3B, a pleiotropic SNP AX-95018072 on chromosome 7A influencing phenology and NDVI, and robust TGW QTNs on chromosomes 2B (qtn_nbpgr_TGW_2B), 1A (qtn_nbpgr_TGW_1A), and 4B (qtn_nbpgr_TGW_4B). Furthermore, annotation revealed that candidate genes near these QTNs encoded stress-responsive proteins, such as chaperonins, glycosyl hydrolases, and signaling molecules. Additionally, three major SNPs AX-95018072 (7A), AX-94946941 (6B), and AX-95232570 (1B) were successfully validated using KASP assay. Conclusion: Our study effectively uncovered novel QTNs and candidate genes linked to heat tolerance and yield-related traits in wheat through an extensive genetic approaches. These QTNs not only corresponded with previously identified QTLs and genes associated with yield traits but also highlighted several new loci, broadening the existing genetic understanding. These findings provide valuable insights into the genetic basis of heat tolerance in wheat and offer genomic resources, including validated markers that could accelerate marker-assisted breeding and the development of next-generation heat-resilient cultivars.